Tolerance to oats in dermatitis herpetiformis. Issue 4 (1st October 1998) - Reunala, T; Collin, P; Holm, K; Pikkarainen, P; Miettinen, A; Vuolteenaho, N; Mäki, M
Abstract : Objectives —Recent studies on coeliac disease have shown that oats can be included in a gluten-free diet without adverse effects on the small bowel. The presence of a rash is also a sensitive indicator of gluten ingestion in dermatitis herpetiformis, and this was used to study whether patients with this disease could also tolerate oats. Patients/Methods —Eleven patients with dermatitis herpetiformis in remission on a gluten-free diet were challenged daily with 50 g oats for six months. Clinical symptoms were recorded, serum samples taken, and skin and small bowel biopsies performed before and after the oat challenge. A control group comprised of 11 patients with dermatitis herpetiformis on a conventional gluten-free diet was also studied. Results —Eight patients challenged with oats remained asymptomatic, two developed a transient rash, and one withdrew because of the appearance of a more persistent but mild rash. Three of the 11 controls also developed a transient rash. IgA endomysial antibodies remained negative in all patients. The small bowel villous architecture, the densities of intraepithelial CD3 and α/β and γ/δ T cell receptor positive lymphocytes and crypt epithelial cell DR expression remained unaltered during the oat challenge. Conclusions —The results confirm the absence of oat toxicity on the gluten sensitive small bowel mucosa and suggest that the rash in patients with dermatitis herpetiformis is not activated by eating oats.